A Genome-Wide Screen Reveals that the Vibrio cholerae Phosphoenolpyruvate Phosphotransferase System Modulates Virulence Gene Expression - Wang, Qiyao (Infect Immun, 2015)
Diverse environmental stimuli and a complex network of regulatory factors are known to modulate expression of Vibrio cholerae's principal virulence factors. However, there is relatively little known about how metabolic factors impinge upon the pathogen's well-characterized cascade of transcription factors that induce expression of cholera toxin and the toxin-coregulated pilus (TCP). Here, we used a transposon insertion site (TIS) sequencing-based strategy to identify new factors required for expression of tcpA, which encodes the major subunit of TCP, the organism's chief intestinal colonization factor. Besides identifying most of the genes known to modulate tcpA expression, the screen yielded ptsI and ptsH, which encode the enzyme I (EI) and Hpr components of the V. cholerae phosphoenolpyruvate phosphotransferase system (PTS). In addition to reduced expression of TcpA, strains lacking EI, Hpr, or the associated EIIA(Glc) protein produced less cholera toxin (CT) and had a diminished capacity to colonize the infant mouse intestine. The PTS modulates virulence gene expression by regulating expression of tcpPH and aphAB, which themselves control expression of toxT, the central activator of virulence gene expression. One mechanism by which PTS promotes virulence gene expression appears to be by modulating the amounts of intracellular cyclic AMP (cAMP). Our findings reveal that the V. cholerae PTS is an additional modulator of the ToxT regulon and demonstrate the potency of loss-of-function TIS sequencing screens for defining regulatory networks.